Intra- and Extracranial Hemorrhagic and Occlusive Vascular Diseases - Frank Reilly; Edwin Allen (Association of American Medical Colleges, 2011)
Abstract This module features web-based animations that were developed in Adobe Flash to simulate the anatomy of the scalp and cranial cavity and some of the common types of intra- and extracranial hemorrhagic and occlusive vascular diseases. They were designed to provide self-directed learning in a structured format that is readily accessible for local and distance learning and computer testing. They serve as an introduction for preclinical students enrolled in medical and dental human structure courses. The simulations are user friendly and achieve a dimension that cannot be attained by using conventional textbooks. They complement didactic and practical (dissection) activities of beginner health care professionals enrolled in human structure courses. Since implementation of the courseware in 2001, 8% more students score correct answers on written exam questions. Learner surveys rate the virtual patient simulations the highest among the resources provided for the human structure courses.